Peningkatan Literasi Dan Numerasi Melalui Pelaksanaan Kampus Mengajar Angkatan Ke-4 Di SMP Swasta Yapena ’45 Medan - Bajongga Silaban; Ninda Dermila Rani Pulungan; Nirmala Dinalias Tafonao; Nora Hesevia Pangaribuan; Novi Aulia Sari; Novita Sari (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The teaching campus program is one of the independent learning independent campus (MBKM) programs in the form of collaborative activities between students and target schools in teaching and developing literacy, numeracy, school administration and technology adaptation skills. This program is implemented in several elementary schools (SD) and junior high schools (SMP) throughout Indonesia, one of which is Yapena'45 Private Middle School in Medan. In this program, students are assigned to assist the school in learning, school administration, and technology adaptation, as well as improving students' literacy and numeracy skills with the programs that have been prepared. The research method used is the participation method by directly involving students in the Yapena'45 private junior high school environment. After making observations, the results of the analysis show that students are still less motivated in learning, especially literacy and numeracy. In addition, the application of technology adaptation in schools is still not related to learning, so it is necessary to help develop several programs to improve students' literacy and numeracy abilities, as well as technology adaptation.